Comparative study of oral terbinafine vs. oral griseofulvin in the management of tinea capitis - Shukla, Anjani Kumar; Bhushan, Bibhuti; Mishra, Dharmendra Kumar; Chaudhary, Shyam Sundar; Jha, Mihir Kumar; Sen, Sukanta (International Journal of Research in Dermatology, 2019)
Background: Tinea capitis (TC) is a common dermatophyte infection affecting primarily prepubertal children. The present study has been designed to assess the clinico-etiological profile of the T capitis and to compare the efficacy and tolerability of terbinafine with griseofulvin. Methods: One hundred fifty eight patients of T. capitis were divided into two groups of 79 patients each to receive either oral griseofulvin or terbinafine (according to weight). Patients in both the groups were followed up at 2, 4, 12 and 36 weeks. At every visit, clinical improvement was evaluated using clinical assessment severity score and the compliance, tolerability and side effects of the drugs were assessed along with KOH microscopy, fungal culture from the lesion and relevant blood investigations. Results: The clinical assessment score were statistically similar in group G and group T at the start of therapy. The decline in scores in both treatment groups was statistically significant at each follow up visit. In griseofulvin group, the mean score was declined from 5.9 at baseline to 4.24 at week 2 and 2.79 at week 4, 0.82 at week 12 and 1.24 at 36 week. In the terbinafine group, the score had a mean of 6.23 at 0 week and 4.03 at week 2, 2.32 at week 4, 0.69 at week 12 and 0.83 at week 36. Conclusions: At follow up study long lasting tissue effect of terbinafine was found but effect of griseofulvin was waned at 36 week. So terbinafine may be better option with similar side effect profile but it is better in residual clinical and mycological effect at higher cost.